Colorimetric detection of Aflatoxin B1 by using smartphone-assisted microfluidic paper-based analytical devices. (February 2022) - Tang, Xuemei; Su, Ruiqi; Luo, Haixi; Zhao, Ying; Feng, Lu; Chen, Jian
Abstract: Aflatoxin B1 (AFB1 ) is a powerful carcinogen, and the pollution it causes has become a global public health safety issue. Therefore, microfluidic paper-based analytical devices (μPADs) with smartphones to read colorimetric signals were constructed for rapid AFB1 detection. The colorimetric mechanism of μPADs was based on the common starch–iodine reaction, and the addition of gelatin/chitosan enhanced the colorimetric effect. During detection and analysis, the competitive analysis occurred in the process of AFB1 monoclonal antibody's recognition of free AFB1 and functionalized antigen. The glucose oxidase-labeled IgG was used as the secondary antibody. Hydrogen peroxide, an oxidation product of the glucose, caused a chroma change in μPADs. Simultaneously, the change in chroma was consistent with the change in AFB1 concentration. Under the best optimized conditions, the limits of detection and quantitation of AFB1 in the buffer were 9.45 and 12.00 ng mL −1, respectively. A comparison of the detection performance of commercial kits with that of the method introduced herein confirmed the superiority of our method in actual food samples with known AFB1 concentrations. This colorimetric μPADs analysis met the detection requirements of some countries, such as China, and had great potential for development in the direction of daily extensive food safety control and environmental monitoring. Graphical abstract: Image 1 Highlights: Portable and low-cost smartphone-based microfluidic paper-based analytical devices (μPADs). The colorimetric μPAD detection system can detect aflatoxin B1 as low as 9.45 ng mL −1 through Lab data analysis. The colorimetric mechanism is based on the common starch–iodine reaction. The addition of gelatin and chitosan mixture enhances the colorimetric effect.